PERHITUNGAN HARGA POKOK PRODUKSI KERIPIK SALAK DAN KERIPIK NANGKA KELOMPOK TANI ADI GUNA HARAPAN KARANGASEM BALI - Suryandari, Ni Komang; Satriawan, I Ketut; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 3 (2015): September, 2015)
Cost of production is an overall charge that is used to create the product in the company. The accuracy of determining the cost of production to be crucial for the company, because the cost of production becomes a reference selling price and affect the company's revenue. The purpose of this study was to calculate all components of the cost production consists of raw material costs, labour costs and factory overhead costs, as well as applying method of determining the cost production for the product salacca and jackfruit chips in Farmers Group Adi Guna Harapan Karangasem Bali. The study used two methods of determining the cost production, that is full costing and variable costing. Results of the study period in February 2015 shows the components of production costs consist of raw material costs, labour costs and factory overhead costs in manufacturing salacca and jackfruit chips. Raw material costs of salacca chips to produce 100 grams packs is Rp 3,732,000,-, jackfruit chips Rp 3,912,000,-, direct labour costs each one Rp 3,348,000,-, factory overhead costs each one Rp 1,560,236,- and non-production costs Rp 1,169,875,-. Cost production of salacca chips with full costing method is Rp 10,000,- with a selling price Rp 12,900,- of 100 grams, while jackfruit chips Rp 10,200,- with a selling price Rp 13,100,- of 100 grams. The cost production of salacca chips with variable costing method is Rp 9,000,- with a selling price Rp 14,300,- of 100 grams, while jackfruit chips Rp 9,200,- with a selling price Rp 14,500,- of 100 grams. Keywords: salacca chips, jackfruit chips, cost production, selling price, full costing, variable costing.
Keywords: 63